2013
DOI: 10.1096/fj.13-240861
|View full text |Cite
|
Sign up to set email alerts
|

Anchored PDE4 regulates chloride conductance in wild‐type and ΔF508‐CFTR human airway epithelia

Abstract: Cystic fibrosis (CF) is caused by mutations in the gene encoding the cystic fibrosis transmembrane conductance regulator (CFTR) that impair its expression and/or chloride channel function. Here, we provide evidence that type 4 cyclic nucleotide phosphodiesterases (PDE4s) are critical regulators of the cAMP/PKA-dependent activation of CFTR in primary human bronchial epithelial cells. In non-CF cells, PDE4 inhibition increased CFTR activity under basal conditions (ΔISC 7.1 μA/cm(2)) and after isoproterenol stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 65 publications
2
32
0
Order By: Relevance
“…Taken together, these data suggest that both correctors modulate the balance between the macromolecular complexes regulating the cAMP signaling machinery in the vicinity of CFTR that either attenuate or enhance its activation (Blanchard et al, 2014;Li and Naren, 2005) and, in this way, restore the cAMP and PKA compartmentalization in the membrane region and improve the cellular environment that has been perturbed by the lack of a functional CFTR on the cell membrane.…”
Section: Discussionmentioning
confidence: 80%
“…Taken together, these data suggest that both correctors modulate the balance between the macromolecular complexes regulating the cAMP signaling machinery in the vicinity of CFTR that either attenuate or enhance its activation (Blanchard et al, 2014;Li and Naren, 2005) and, in this way, restore the cAMP and PKA compartmentalization in the membrane region and improve the cellular environment that has been perturbed by the lack of a functional CFTR on the cell membrane.…”
Section: Discussionmentioning
confidence: 80%
“…Sodium current was blocked with amiloride. Cells incubated with 10 mM VX-809 alone (Blanchard et al, 2014) showed increased short-circuit current in response to forskolin and genistein, which was inhibited by CFTR inh -172 (Fig. 7A).…”
Section: Cfbe41omentioning
confidence: 98%
“…PDE4 family, the primary cAMP-specific enzyme, comprises four genes (PDE4A-D), each with multiple variants that encode more than 20 different protein products (8). The therapeutic potential of PDE4 inhibition in airway inflammatory diseases such as chronic obstructive pulmonary disease (COPD), asthma, and cystic fibrosis (CF) has long been explored (9)(10)(11)(12). Recently, roflumilast has been approved as the first PDE4 inhibitor for oral, once-daily treatment of severe COPD with symptoms of chronic bronchitis and a history of exacerbations (12)(13)(14).…”
mentioning
confidence: 99%